The contribution of sense of place and local identity in designing an urban lifestyle center in Davao City - Abiera, Anne Lorraine F. (2019)
An urban lifestyle center, defined by the International Council of Shopping Centers (ICSC), is a multi-purpose leisure-time destination, including restaurants, entertainment, and design ambiance and amenities such as fountains and street furniture that are conducive to casual browsing. This research studies the theories of sense of place and local identity in application to the design of an urban lifestyle center. This study employed the following theories: (1) Suzanne Bott?s sense of place theory was employed in this stud, which has domains and scales that factor to the emotional involvement of a person to a place; (2) Yuhan Shao?s theory on local identity which derived the concepts into four aspects which are the physical aspect, social aspect, sensory aspect, and memory aspect. The data were gathered through direct observations, surveys, and interviews among the seven lifestyle center in Davao City. The correlation between the results on sense of place and local identity were measured through the pearson product-moment correlation and was analysed through descriptive statistics. The findings on the study stated that urban lifestyle centers should have the qualities of walkability, which are connectivity, good circulation, and parking areas. Circulation especially on open spaces must be considered in the design. Among the seven urban lifestyle center studied, Matina Town Square (MTS) is the center with the highest sense of place. The research concludes that local identity and sense of place are important and related theories in architecture, especially in the study of the relationship of the users to the place."
Thesis (BS Architecture)--University of the Philippines Mindanao, 2019